1970
DOI: 10.3126/njog.v3i1.1435
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of labour progress and delivery outcome among induced versus spontaneous labour in nulliparous women using modified WHO partograph

Abstract: Aim: Induced or spontaneous labour has implication on the eventual mode of delivery and neonatal outcome. The objective of this study is to compare the progress and outcome of induced versus spontaneous labour among nulliparous women using the modified WHO partograph. Methods: Comparative study involving nulliparous women in active phase of labour with the cervix at least 4cm dilated. Those whose labours were induced were compared with those on spontaneous labour; both labouring women were monitored using modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
11
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 1 publication
7
11
1
2
Order By: Relevance
“…8 The mean total duration of labour among comparison group was similar (6.080 versus 6.507 hours). This is less that the mean duration of 8.83 hours reported among primigravidae in spontaneous labour in uncomplicated pregnancies but comparable to the study conducted by Orji EO et al 9 We found that more women in the induced group crossed action line as compared to spontaneous group and this was found statistically significant (p=0.02). Present study was comparable to a study done by Orji EO et al in which they also found similar results i.e.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…8 The mean total duration of labour among comparison group was similar (6.080 versus 6.507 hours). This is less that the mean duration of 8.83 hours reported among primigravidae in spontaneous labour in uncomplicated pregnancies but comparable to the study conducted by Orji EO et al 9 We found that more women in the induced group crossed action line as compared to spontaneous group and this was found statistically significant (p=0.02). Present study was comparable to a study done by Orji EO et al in which they also found similar results i.e.…”
Section: Discussionsupporting
confidence: 77%
“…55.1% patients had normal active phase, 27.9% patients moved between alert and action line and 16.9% patients reached or crossed action line in spontaneous group while 57.4% patients had normal active phase 9.6% patients moved between alert and action line and 33.1% patients reached or crossed action line in induced group. 9 Regarding mode of delivery, spontaneous onset of labour had more vaginal delivery compared to induced labour group while vice versa for caesarean section. Present results were similar to the study done by Orji EO et al and Yadav P et al in which they concluded that larger proportion of women in spontaneous group had vaginal delivery compared to induced group and also lesser proportion of caesarean section in spontaneous group.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to studies on the use of the partograph done in other settings [10,[15][16][17][18], completion to standard (as defined earlier) in this study is relatively better, although not acceptable. The various labour parameters were recorded to standard in 32.5%-79.4% of cases, with the least standard recording in moulding of fetal skull and the highest in maternal demographics.…”
Section: Discussioncontrasting
confidence: 54%
“…Orji EO et al conducted a study and they found that induced group had better APGAR at one and five minutes compared to spontaneous group. 8 A study done by Selo-Ojeme D et al, in which they concluded that Apgar <5 at 5 minutes was more common in induced group compared to spontaneous group. 6 For maternal complications also, both groups had similar events.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were similar to the study done by Orji EO et al, in which they concluded that larger proportion of women in spontaneous group had vaginal delivery compared to induced group and also lesser proportion of caesarean section in spontaneous group. 8 Alyasin ZT et al, conducted a study and they compared elective labour induction with spontaneous onset of labour in post-dated pregnancy and they concluded that rate of caesarean section was more in induced group. 7 In a study done by Jankiraman V et al, they concluded that induced nulliparous had increased rate of caesarean section compared spontaneous onset labour.…”
Section: Discussionmentioning
confidence: 99%